Extinction in a Nonautonomous Discrete Lotka-Volterra Competitive System with Time Delay - Meng Hu; Jingyuan Wei (Discrete Dynamics in Nature and Society)
This paper is concerned with a nonautonomous discrete Lotka-Volterra competitive system with time delay. By using some analytical techniques, we prove that, under certain conditions, one of the species will be driven to extinction while the other one will be globally attractive with any positive solution of a discrete logistic equation.